188k views
4 votes
How do you balance Sb+I2=SbI3 show work please

1 Answer

3 votes

Answer:

2Sb + 3I₂ → 2SbI₃

Step-by-step explanation:

The reaction expression we need to balance is:

Sb + I₂ → SbI₃

To balance this expression, we need to assign the variables a,b and c to each specie as the coefficient that will balance the expression.

aSb + bI₂ → cSbI₃

Conserving Sb : a = c

I : 2b = 3c

let a = 1, c = 1, b =
(3)/(2)

Multiply through by 2;

a = 2, b = 3 and c = 2

2Sb + 3I₂ → 2SbI₃

User Manan Vaghasiya
by
5.6k points